From Acidified Groves to Virtual Mountains. The Continuum of Utopian Landscape Types In Twenty-First-Century Nordic Art - Roivainen Hilja (Brill Rodopi, 2025)
I argue in this article that, firstly, a selected case of Nordic painters: Anna Tuori (FI, 1976), Petri Ala-Maunus (FI, 1970) and John Kørner (DK, 1967), problematise in their twenty-first-century paintings the historically utopian topoi of landscapes, such as the paradise and Arcadia. This is done by repeating the topoi’s landscape iconography. Secondly, the paintings renew this iconography by mixing it with dystopian moods and elements, such as the emotive colour moods and visual signs from the contemporary living world. For example, painters use ironically intertextual references to various clichéd meanings and forms of consumption, that have been attached to the utopian landscape types, such as, the leisure industries’ marketing imagery. The utopian Arcadian, pastoral or sublime landscape types are translated in these paintings into simulacra of imagined reality (Baudrillard 1994), and turned into mere aesthetic triggers, that formally compose the painting. Often abstract marks or patches and colour moods contrast the presented utopian landscape views, and thus dialectically confuse or distance the spectator from the utopian scene. Thirdly, the landscape paintings formulate a hermeneutical understanding of the global world and exemplify philosopher Ernst Bloch’s (1986) concept of a wishful landscape. I claim that what makes these paintings, in a contradictory way, ecocriticism, is that they contemplate nature aesthetically and emotionally. Through an iconographical-intellectual historical analysis I define the aporic and ecocritical role that these painted utopian–dystopian landscapes take. I build my interpretation and analyse the ideas of utopian landscapes, from a Marxist perspective on landscape art, in the light of the research by human geographer Denis E. Cosgrove (1998), literary scholar Raymond Williams (2016), philosopher Ernst Bloch (1885–1977; 1986) and cultural theorist Malcolm Miles (2014). The themes pointed out by Cosgrove (1998 and 2008): the individual perspective, the emotional understanding of the world or self, both in European colonialist and romantic thought, and “the landscape way of seeing” are visible in the discussed paintings.
Landscapes of Affect and Emotion. Nordic Environmental Humanities and the Emotional Turn.